PERAN KEPALA SEKOLAH DALAM MENGEMBANGKAN KOMUNITAS BELAJAR UNTUK MENINGKATKAN KINERJA GURU DI SD NEGERI 2 WAISAI - Jackline Tifani Lamia; Robert Masreng; Monika Gultom (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to analyze the role of the principal in improving teacher performance through the development of learning communities at SD Negeri 2 Waisai, Raja Ampat Regency. This research is motivated by the importance of the principal’s leadership as instructional leadership in building a collaborative and reflective school culture. This study employs a qualitative approach with a descriptive research design. The research informants consist of the principal, teachers, the head of the learning community, school supervisors, and students. Data collection techniques were conducted through in-depthinterviews, participatory observation and documentation. Data analysis used the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data display and conclusion drawing. Data validity was ensured through source and method triangulation. The results of the study show that principal performs leadership roles based on the EMASLIM theory, particularly as an educator, supervisor, leader and innovator in developing learning communities. Tehse roles encourage teacher collaboration, learning reflection and innovation in teaching practices. This study concludes that professional learning communities significantly contribute to improving teacher performance and strengthening a collaborative.